2014
DOI: 10.1186/s12302-014-0014-5
|View full text |Cite
|
Sign up to set email alerts
|

Republished study: long-term toxicity of a Roundup herbicide and a Roundup-tolerantgenetically modified maize

Abstract: BackgroundThe health effects of a Roundup-tolerant NK603 genetically modified (GM) maize (from 11% in the diet), cultivated with or without Roundup application and Roundup alone (from 0.1 ppb of the full pesticide containing glyphosate and adjuvants) in drinking water, were evaluated for 2 years in rats. This study constitutes a follow-up investigation of a 90-day feeding study conducted by Monsanto in order to obtain commercial release of this GMO, employing the same rat strain and analyzing biochemical param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
149
1
13

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(174 citation statements)
references
References 64 publications
11
149
1
13
Order By: Relevance
“…Mesnage et al [42] identified over 4000 genes related to liver and kidney function whose expression rates were significantly altered, and this was consistent with anatomical and histological changes as well as blood and urine biochemical pathologies identified by Séra-liniet al for rats similarly exposed [43]. Mesnage et al [42] wrote in the abstract: "Observed alterations in gene expression were consistent with fibrosis, necrosis, phospholipidosis, mitochondrial membrane dysfunction and ischemia."…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Mesnage et al [42] identified over 4000 genes related to liver and kidney function whose expression rates were significantly altered, and this was consistent with anatomical and histological changes as well as blood and urine biochemical pathologies identified by Séra-liniet al for rats similarly exposed [43]. Mesnage et al [42] wrote in the abstract: "Observed alterations in gene expression were consistent with fibrosis, necrosis, phospholipidosis, mitochondrial membrane dysfunction and ischemia."…”
Section: Discussionmentioning
confidence: 60%
“…Such a complex would be very similar to bisphosphonates in that both molecules contain two phosphonyl groups. Glyphosate has been linked to multiple myeloma [67] and to multiple other cancers and therefore to chemotherapy [33] [34], and there is strong support in the literature for glyphosate causing renal impairment [28] [43]. Low plasma proteins, such as serum albumin and transferrin, are associated with pulmonary vascular permeability [68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Glyphosate also impairs metabolism of toxic phenolic compounds such as nonylphenols, diethylstilbestrol, and bisphenol A; all widely recognized to possess estrogenic activity, thus having an indirect potential impact on increasing risk of breast cancer. 20 Use of glyphosate possesses a real possible risk linking development of BC and EOC.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Originally, these findings appeared in the journal Food and Chemical Toxicology in September 2012, but the paper was retracted by the journal's editor in November 2013. The paper republished a year later (Seralini et al, 2014). Recently, glyphosate was shown to induce birth defects in rats (Guerrero Schimpf et al, 2016) and was suggested (without experimental evidence) to produce DNA and epigenetic effects (Nardemir et al, 2015), and to act as the analogue of the amino acid glycine to replace it in diverse proteins (Samsel and Seneff, 2016).…”
Section: Fate In the Environment And Side Effectsmentioning
confidence: 99%